Detection of Virulence-Associated Genes and in vitro Gene Transfer From Aeromonas sp. Isolated From Aquatic Environments of Sub-himalayan West Bengal - Mangar, Preeti; Barman, Partha; Kumar, Anoop; Saha, Aniruddha; Saha, Dipanwita (Frontiers in Veterinary Science, 2022)
Aeromonas are omnipresent in the aquatic environments and cause disease within a wide host range. Thirty-four isolates from water samples of small fish farms were identified as Aeromonas based on biochemical characteristics and 16S rRNA gene sequence. Six virulent factors were analysed which indicated 100% of isolates as beta-hameolytic and proteolytic, whereas 44.1%, 38.2% and 70.6% isolates produced DNAse, siderophores and amylase respectively. Studies on occurrence of four genetic determinants of virulence factors revealed that aer/haem (haemolytic toxin) and flaA (polar flagella) genes were present in 44.1% strains whereas ascV (Type3 secretion system) and aspA (serine protease) genes were detected in 21.5% and 8.82% of strains respectively. Fish (Anabas testudineus) challenge studies showed isolate GP3 (Aeromonas veronii) bearing five virulent factors with combination of aer/haem+/ascV+/fla+ genes induced severe lesions leading to 100% mortality. In contrast, RB7 possessing four virulence factors and three genes (aer/haem+/ascV+/aspA+) could not produce severe lesions and any mortality indicating absence of correlation between the virulence factors, its genes and the pathogenicity in fishes. GP3 was cytotoxic to human liver cell line (WRL-68) in trypan blue dye exclusion assay. The 431 bp aer/haem gene of GP3 was transferable to E.coli Dh5α with a conjugational efficiency of 0.394 × 10-4 transconjugants per recipient cell. The transfer was confirmed by PCR and by the presence of 23kb plasmids in both donor and transconjugants. Therefore, occurrence of mobile genetic elements bearing virulence associated genes in Aeromonas indicates the need for periodic monitoring of the aquatic habitat to prevent disease outbreak.